DEVELOPING THE INFORMATION LITERACY-BASED CURRICULUM FOR TEACHER EDUCATION - Winangun, Muhammad Mamduh; Darmawan, Deni (EDUTECH, 2019)
The ability of information literacy is very important for teachers in carrying out their duties and functions because it is related to the teacher's ability to find, access, and evaluate information. In addition, information literacy skills are also related to lifelong learning that teachers need to improve their competence independently. Information literacy competencies need to be established through education and training in universities. Some studies have found that the teacher's literacy ability is still low. It takes an effort to prepare teacher candidates who have information literacy skills, one of which is by developing an information literacy-based curriculum (ILbC) for teacher education. In this article, the author studies literature related to curriculum concepts, organizations, models, designs and curriculum structure based on information literacy for teacher education. Base on the analysis, the ecletic (combination of cognitive process and technological concept) concept, integrate curriculum organization, Walker model, and problem centered design is appropriate fo developing ILbC. The curriculum structure is also presented. This curriculum is expected to be an alternative to develop information literacy skills of prospective teacher students.Kemampuan literasi informasi sangat penting bagi guru dalam menjalankan tugas dan fungsinya karena berkaitan dengan kemampuan guru dalam mencari, mengakses, dan mengevaluasi informasi. Selain itu, keterampilan literasi informasi juga berkaitan dengan pembelajaran sepanjang hayat yang dibutuhkan guru untuk meningkatkan kompetensinya secara mandiri. Kompetensi literasi informasi perlu dibentuk melalui pendidikan dan pelatihan di perguruan tinggi. Beberapa penelitian menemukan bahwa kemampuan literasi guru masih rendah. Dibutuhkan upaya untuk mempersiapkan calon guru yang memiliki keterampilan literasi informasi, salah satunya dengan mengembangkan kurikulum berbasis literasi informasi (ILbC) untuk pendidikan guru. Pada artikel ini, penulis mengkaji literatur terkait konsep kurikulum, organisasi, model, desain dan struktur kurikulum berbasis literasi informasi untuk pendidikan guru. Berdasarkan analisis, konsep ekletik (kombinasi proses kognitif dan konsep teknologi), integrasi organisasi kurikulum, model Walker, dan desain yang berpusat pada masalah sesuai untuk mengembangkan ILbC. Struktur kurikulum juga disajikan. Kurikulum ini diharapkan dapat menjadi alternatif untuk mengembangkan keterampilan literasi informasi siswa calon guru.